29+1. La ordenación urbanística metropolitana de Gran Valencia (1947-1986) - Selva Royo, Juan Ramón (2013)
The present research analyses the Mediterranean city of Valencia from a territorial point of view, immediately following the establishment of the Administrative Corporation Gran Valencia by the Act of 10th February 1947.